Effect of Drug Information Service on Clinical Outcome of Patients with Type 2 Diabetes Mellitus in Padang, Indonesia - Lailaturrahmi Lailaturrahmi; Fuji Araswati; Armenia Armenia; Rahmi Yosmar (Borneo Journal of Pharmacy, 2022)
Type 2 diabetes mellitus (T2DM) has been a health burden worldwide, including Indonesia. However, T2DM therapy needs a long and complex process, which patients often do not favor, thus making them does not take medications as instructed and negatively affecting clinical outcomes. This study aimed to understand the effect of Drug Information Service provision on the clinical outcome of T2DM patients. This quasi-experimental study was conducted using one group pre-post-test design. As the clinical outcome, the fasting blood glucose levels were measured before and after the intervention. A drug information service was provided through direct explanation to the patients. Sociodemographic data were analyzed descriptively. The difference in fasting blood glucose before and after the intervention was assessed using Wilcoxon signed-rank test. Forty patients participated in this study. Most participants are female (N=34; 85%) and receive two-drugs combination therapy of metformin and sulfonylureas (N=32; 77.5%). Although there is a decrease in mean fasting blood glucose level after intervention (174.92±59.561 vs. 184.20±49.768), there is no significant difference between fasting blood glucose levels pre-intervention and post-intervention (p>0.05). It is concluded that despite the noticeable decline of blood glucose level after drug information service, its effect on blood glucose control is not significant.